Bioreactors Land-Fills (BRLFs) for Waste Treatment. (1) Its Main Characteristics and Advantages. - Hamed Elnashaie, Said Salah Eldin; Ahmadun, Fakhru'l-Razi; Ismail, Mohd Halim Shah; Danafar, Firoozeh; Baojahmadi, Mina (2013)
Bio-Reactors Landfills (BRLFs) represent important advancements over the classical Dry Land-Fills (DLFs) which are oldest technology for disposal of solid waste; specially Municipal Solid Waste (MSW). The combined use of laboratory experimental work and mathematical/ computer modeling represents the best way for scaling-up to the design of commercial units and optimization of design and operation. This is the first part of a series of papers that introduces these relatively modern BRLFs ; its main characteristics and the basic principles for its mathematical modeling using chemical reaction engineering rules in a rigorous manner. It also gives a couple of commercial cases to materialize the principles presented in the paper.